(untitled) (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2024)
The success of a company is highly dependent on its marketing strategy, which must describe clear and measurable steps to take advantage of opportunities in the target market. Toko Matahari Mandiri Perkasa uses a marketing mix to increase the number of consumers, retain customers, and increase sales, so that it can generate profits that support the company’s long-term sustainability. This study aims to evaluate how much influence the marketing mix has on sales volume at Toko Matahari Mandiri Perkasa. The research method used is quantitative research, collecting data through questionnaires, observations, and documentation. The population and sample in this study were all leaders and employees of CV. Matahari Mandiri Perkasa as many as 35 people. The results of the study explain that based on hypothesis testing, it turns out that the marketing mix variable has a very important influence on increasing sales volume. Because tcount> ttable, namely 8.30> 2.70, so it can be stated that the marketing mix can affect the increase in sales volume at CV. Mandiri Perkasa. Thus the hypothesis (Ha) is accepted, namely "There is an Influence of Marketing Mix on sales volume at CV. Matahari Gunungsitoli".